Effects of customer incivility on burnout: A moderated mediation model - Carvalho, F.; Silva, S.A.; Di Marco, D.; Carvalho, H.; Schaufeli, W. B. (Work, Stress, and Health 2021 Conference, 2021)
Using data from a public Institution, we analysed the effect of customer incivility on burnout and how trust and organisational justice mediate and moderate this relationship. At lower levels, justice moderated the association between incivility and trust; and of incivility on burnout (three of four dimensions) via trust. By not being perceived as fair, organisations risk having employees that- exposed to customer incivility- experience greater consequences on their well-being.